Analisis Sistem Informasi Akuntansi Simpan Pinjam Sebelum Dan Setelah Menggunakan Metode Rapid Application Development (RAD) Pada KPRI Dhaya Harta Jombang - Giri Pramesty, Wahyuning; Taufik Hidayat, Agus (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The Accounting Information System is a form of accounting information system that concentrates on the process of creating, presenting and improving information to the authorities managing business activities to be used as a basis for policy making. Rapid Application Development (RAD) is a software development process model that is classified as an incremental (multilevel) technique. RAD emphasizes short, concise, and rapid development cycles. This research aims to create a model (prototype) for designing a savings and loan accounting information system using the Rapid Application Development (RAD) model at KPRI Dhaya Harta Jombang. In this research, we analyze the savings and loan procedures that run at the KPRI Dhaya Harta Jombang cooperative according to the stages of the Rapid Application Development (RAD) method. Analysis of problems in cooperatives is described in a system flowchart for each running procedure.